Psychological Aspects of Pedagogical Practice. To the 100th Anniversary of Nina F. Talyzina - Marina A. Stepanova (Lomonosov Moscow State University, 2024)
Background. The article is dedicated to the 100th anniversary of the birth of Nina Fedorovna Talyzina (1923-2018) - a famous Russian (Soviet) psychologist, specialist in the field of didactics and psychology of teaching and learning, one of the students and followers of P.Y. Galperin, author of the activity theory of learning, creator of the Department of Pedagogy and Educational Psychology at the Faculty of Psychology of Lomonosov Moscow State University Objectives. The focus of the article is on the restoration of the scientific biography of N.F. Talyzina as well as on the identification of the main directions of research carried out under her leadership and with her direct participation. Methods. In this historical and psychological research, the oral and written speeches of N.F. Talyzina, as well as biographical and archival materials were analysed. Results. The article presents the main stages of the scientific biography of N.F. Talyzina. N.F. Talyzina completed her Cand. Sci. (Psychology) thesis on the topic "Inferences in solving geometric problems" under the supervision of P.A. Shevarev at the graduate school of the Research Institute of Psychology of the Academy of Pedagogical Sciences of the RSFSR (now PI RAO). After defending the thesis in 1950 she began working at Moscow University. At Lomonosov Moscow State University N.F. Talyzina made her way from assistant (1950-1952), senior lecturer (1952-1960), associate professor (1960-1963) of the Department of Psychology of the Faculty of Philosophy to the head of the Department of Pedagogy of Humanities Faculties (1963-1966), and then head of the Department of Pedagogy and Educational Psychology (1966-1995) of the Faculty of Psychology created in 1966. In 1970, N.F. Talyzina defended her doctoral dissertation on the topic "Psychological foundations of managing knowledge acquisition." In 1989, on the initiative of N.F. Talyzina a Training Center for retraining university employees in the field of psychological and pedagogical foundations of the educational process in higher education at the Faculty of Psychology of Lomonosov Moscow State University was created. In 1995 N.F. Talyzina left the post of the head of the department and for 20 years until 2015 she remained a professor at the above-mentioned Training Center. From 2015 until the end of her life N.F. Talyzina was a leading researcher at the Laboratory of Educational Psychology at the Department of Psychology of Education and Pedagogy. Conclusions. The ideas about the controlled formation of concepts developed by N.F. Talyzina not only received experimental testing, but were also used in organizing school and vocational instruction.